Kerk en teologie in die postmoderne tyd - Toit, P. W. du (HTS teologiese studies, 2002)
Church and theology in the postmodern eraThe postmodern era has wide implications for church and theology. This study is an endeavour to participate in the discourse on these implications. It reflects on what is entailed by postmodernism and how the new era influences church and theology. It also reflects on the interpretation of the Bible, the status of the Reformed confessions and the dialogues in which pastors engage in their congregations.